Hubungan antara Keterampilan Literasi Awal dengan Kemampuan Bahasa Pragmatik pada Anak Umur Prasekolah di Taman Kanak-Kanak Marsudirini Surakarta - Prestarini, Sania; Nugroho, Setyadi (Jurnal Terapi Wicara dan Bahasa, 2023)
ABSTRACT Background: In 2018, Indonesia is still faced with child development problems. There are around 56.34% of preschoolers experiencing delays in developments such as reading and writing. The development of literacy is important to pay attention to and in early childhood development, language really needs to be developed considering the importance of language for all of us. Viewed from the aspect of language, pragmatics is the highest stage of language, pragmatics is a branch of linguistics that discusses what is included in the structure of language as a means of communication between speakers and listeners. Objective: This research aims to find out the correlation between early literacy skills and pragmatic language skills in preschool-aged children in TK Marsudirini Surakarta. Method: The type of research used is quantitative. The research design to be used is a correlational study. The sampling technique that will be used in this research is purposive sampling. The number of samples that have been used in this research were 30 respondents. Result: The results showed that 6 respondents (20%) were in the early literacy skills category, the sufficient category was 11 respondents (36.7%), and the good category was 13 respondents (43.3%). Respondents in pragmatic language skills in the unable category were 14 respondents (46.7%) and in the able category were 16 respondents (53.3%). Bivariate analysis used the Spearman Rank statistical test with a ???? value of 0.001 and a correlation coefficient of 0.732. This shows that the direction of the correlation between the two variables is positive, which means that if one variable increases, the other variable will develop. Conclusion: There is a correlation between early literacy skills and pragmatic language skills in preschool-aged children in TK Marsudirini Surakarta with a strong correlation strength. Keywords: Literacy Skills, Pragmatic Language, Preshool Children